Does truancy make the delinquent? A situational and longitudinal analysis of the truancy–delinquency relationship - Gerth, Maria (European journal of criminology, 2022)
Although truancy has frequently been linked to delinquency, we still lack a proper understanding of how this relationship comes about. This study uses Situational Action Theory (SAT) to develop a more comprehensive, mechanism-based explanation of the truancy?delinquency nexus. The core argument is that the relationship is conditional on adolescents? propensity for delinquency and their exposure to criminogenic settings. To test this argument, I use two kinds of data collected as part of the Peterborough Adolescent Development Study (PADS+). Drawing on unique situational data provided by space?time budgets, I find only weak evidence that the relationship between truancy and delinquency exists at the situational level. Analyses of multiple yearly waves of this panel study provide support for SAT?s potential as a theoretical framework for the truancy?delinquency relationship by showing that the effect of truancy on changes in delinquency is conditional on changes in adolescents? delinquency propensity and their exposure to criminogenic settings.